Negative pole piece and preparation method thereof, battery monomer and power utilization device
Patent Information
- Application Number
- CN202310796833.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
Smart Images

Figure CN119230829A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology, and specifically relates to a negative electrode plate and a preparation method thereof, a battery cell and an electrical device. Background Art
[0002] Battery cells, also called rechargeable batteries, are batteries that can be repeatedly discharged and charged and used multiple times. In recent years, as battery cells represented by lithium-ion batteries have been increasingly widely used, people have put forward higher requirements for their performance, especially cycle performance.
[0003] Therefore, further improving the cycle performance and storage performance of battery cells remains a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode plate, which can improve the cycle performance of a battery cell containing it; the purpose of the present application is also to provide a battery cell and an electrical device containing the above-mentioned positive electrode plate, so as to obtain improved battery cell cycle performance and storage performance.
[0005] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising:
[0006] Negative electrode current collector,
[0007] a negative electrode active material layer disposed on at least one side of the negative electrode current collector; and
[0008] The functional coating is disposed on the side of the negative electrode active material layer away from the negative electrode current collector, wherein the functional coating comprises a chalcogenide material, and the chalcogenide material comprises elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
[0009] The technical solution of the embodiment of the present application provides a negative electrode sheet, wherein the negative electrode active material layer of the negative electrode sheet is provided with a functional coating on the side away from the negative electrode current collector, and the functional coating comprises a specific chalcogenide material. Unexpectedly, when a battery cell comprising the negative electrode sheet according to the embodiment of the present application is formed, an SEI film having excellent elasticity and stability can be formed on the surface of the negative electrode sheet.
[0010] Without intending to be limited to any theory or explanation, when the above-mentioned battery cell is formed, the functional coating contacts and interacts with the electrolyte (including a cyclic carbonate solvent such as ethylene carbonate), so that the sulfide material participates in the formation of the SEI film, and the components of the SEI film formed thereby may include alkyl sulfates and polyoxyalkylene polymers (such as polyethylene oxide (PEO)), etc., so that the SEI film has excellent elasticity and stability. Such an SEI film can accommodate and adapt to the volume change caused by the rebound of the negative electrode sheet containing the negative electrode active material layer, reduce or avoid the negative electrode sheet squeezing the structure containing the SEI film in the battery cell and thus causing structural damage, reduce the risk of the SEI film being repeatedly damaged and continuously re-formed, and improve the interface stability between the negative electrode active material and the electrolyte, thereby improving the cycle performance and storage performance of the battery cell containing the negative electrode sheet.
[0011] In addition, the solid electrolyte interface membrane with excellent elasticity can stabilize the interface stability between the negative electrode plate and the electrolyte, thereby increasing the service life of the battery cell.
[0012] In addition, the solid electrolyte interface membrane formed with the participation of chalcogenide materials has good active ion permeability, which can promote the rapid transmission of active ions at the interface and improve the ion transmission rate. After the chalcogenide materials in the functional coating of the negative electrode plate participate in the solid electrolyte interface membrane, the porosity in the functional coating is improved, and the transmission rate of active ions in the negative electrode plate is improved, thereby comprehensively improving the kinetic performance of the battery cell containing the negative electrode plate.
[0013] In some optional embodiments, the functional coating includes 30% to 95% of the chalcogenide material based on the total mass of the functional coating.
[0014] According to the embodiments of the present application, the sulfide material containing the above-mentioned mass content can improve the elasticity of the solid electrolyte interface membrane, can accommodate and adapt to large volume changes of the negative electrode pole piece containing the negative electrode active material layer, reduce or avoid the negative electrode pole piece squeezing the structure containing the solid electrolyte interface membrane in the battery cell and thereby causing structural damage, reduce the risk of the solid electrolyte interface membrane being repeatedly destroyed and continuously reformed, thereby improving the cycle performance of the battery cell containing the negative electrode pole piece.
[0015] In some optional embodiments, the ratio of the thickness of the negative electrode active material layer to the thickness of the functional coating layer is 1:
[0016] (0.01~0.2). The option is 1: (0.01~0.1).
[0017] According to the embodiment of the present application, the ratio of the thickness of the negative electrode active material layer to the thickness of the functional coating layer is controlled within the above range, so that the functional coating layer can provide a sufficient protective layer to protect the negative electrode active material. The components such as metal selenide, sulfur and selenium can form a protective layer to prevent the negative electrode active material from directly contacting the electrolyte, reduce the side reaction with the electrolyte, and improve the cycle stability of the battery cell containing the negative electrode plate.
[0018] In some optional embodiments, the thickness of the functional coating is 1 to 10 um; optionally, 2 to 5 um.
[0019] According to the embodiment of the present application, the functional coating has a thickness within the above range, which is beneficial to the embedding and de-embedding of active ions of the negative electrode plate in the battery cell, and is beneficial to the dynamic performance and cycle performance of the battery cell.
[0020] In some optional embodiments, the average particle size D50 of the chalcogenide material is 50 to 500 nm; optionally, 100 to 300 nm.
[0021] According to the embodiment of the present application, the average particle size Dv50 of the chalcogenide material is within the above range, which is conducive to the participation of the chalcogenide material in the formation of a solid electrolyte interface film in the battery monomer formation, and the formation of evenly distributed pores with relatively uniform particle size after decomposition from the negative electrode active material layer, which is conducive to the structural stability of the functional coating and the dynamic performance and cycle performance of the battery monomer. In some optional embodiments, the porosity of the functional coating is 15% to 40%.
[0022] According to the application embodiment, the functional coating has a porosity within the above range, which is beneficial for the electrolyte to infiltrate the functional coating during the formation stage, and facilitates the sulfide material in the functional coating to participate in the formation of a solid electrolyte interface film, thereby making the solid electrolyte interface film have stronger elasticity.
[0023] In some optional embodiments, the functional coating includes a chalcogenide material, a conductive agent, and a binder.
[0024] According to an embodiment of the present application, when the functional coating comprises a chalcogenide material, a conductive agent and a binder. x S y 、M x Se y 、M x Te y It can be used as negative electrode active material, with high lithium / sodium insertion capacity, and the entire functional coating can be used as another new negative electrode active material layer to improve the cycle performance of the battery cell. Sulfur, selenium and tellurium in chalcogenide materials can also be used as negative electrode active materials.
[0025] In some optional embodiments, the functional coating includes 5% to 10% of the conductive agent based on the total mass of the functional coating.
[0026] According to the embodiments of the present application, when the functional coating contains the conductive agent in the above-mentioned content, the internal resistance of the negative electrode plate can be reduced, and the internal resistance of the entire battery cell can be reduced, which is beneficial to the transmission of electrons and improves the dynamic performance of the battery cell containing the negative electrode plate.
[0027] In some optional embodiments, the functional coating includes 3% to 5% of the binder based on the total mass of the functional coating.
[0028] According to the embodiment of the present application, when the functional coating has the above-mentioned binder content, the structural stability, electrical conductivity and ion transport performance of the negative electrode plate can be balanced. However, too high or too low a binder content may affect the performance of a battery cell including the negative electrode plate.
[0029] In some optional embodiments, based on the total mass of the functional coating, the functional coating comprises 85% to 92% of a chalcogenide material containing a metal element, 5% to 10% of a conductive agent, and 3% to 5% of a binder, wherein the chalcogenide material containing a metal element comprises M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
[0030] According to an embodiment of the present application, the functional coating comprises the above-mentioned content of a chalcogenide material containing a metal element, the above-mentioned content of a conductive agent and the above-mentioned content of a binder. When the negative electrode plate comprising the above-mentioned functional coating is formed, the functional coating has a larger porosity. The chalcogenide material containing a metal element as a negative electrode active material has good electronic conductivity and can quickly transfer electrons. It usually has a sub-stoichiometric composition, that is, the ratio of metal to chalcogenide elements including selenium deviates from the stoichiometric ratio. This sub-stoichiometric ratio can provide more embedding / de-embedding sites, promote faster ion transport and higher electrochemical reaction rates, and can improve the electrochemical reaction kinetics of the battery cell to achieve high power output and fast charge and discharge rates.
[0031] In some optional embodiments, the negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon, a silicon-carbon composite material, and a silicon-oxygen material.
[0032] According to the embodiment of the present application, the negative electrode active material layer including the above silicon-based material is in the negative electrode plate, which can improve the capacity of the battery cell including the negative electrode plate and realize rapid ion diffusion.
[0033] In some optional embodiments, the negative electrode active material layer includes 1% to 50% of silicon element based on the total mass of the negative electrode active material layer.
[0034] According to the embodiment of the present application, adding the above-mentioned silicon element can increase the capacity of the negative electrode active material, thereby improving the energy density of the battery. Silicon has a high electrical conductivity, and adding an appropriate amount of silicon element can enhance the electronic conductivity of the negative electrode active material layer; silicon-based materials have a high ion diffusion coefficient, and the introduction of an appropriate amount of silicon element can promote the rapid transmission of active ions in the negative electrode active material, thereby improving the battery's kinetic performance, including the charge and discharge rate.
[0035] Method for preparing negative electrode sheet
[0036] In a third aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising:
[0037] A first slurry containing a chalcogenide material and a second slurry containing a positive electrode active material are provided, wherein the chalcogenide material includes elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2;
[0038] The first slurry and the second slurry are coated on one side of the negative electrode current collector to form a functional coating and a negative electrode active material layer, respectively, to obtain the negative electrode plate of the first aspect or the second method, wherein the negative electrode plate includes a negative electrode active material layer arranged on at least one side of the negative electrode current collector and a functional coating arranged on a side of the negative electrode active material layer away from the current collector.
[0039] According to the embodiments of the present application, by respectively forming a functional coating and a negative electrode active material layer with a composition comprising a chalcogenide material and a positive electrode active material, the chalcogenide material in the negative electrode plate can participate in forming a solid electrolyte interface membrane. The solid electrolyte interface membrane has the participation of chalcogenide elements, which enhances the elasticity of the solid electrolyte interface membrane and can accommodate and adapt to large volume changes of the negative electrode plate comprising the negative electrode active material layer, thereby reducing or avoiding the negative electrode plate squeezing the structure comprising the solid electrolyte interface membrane in the battery cell and thereby causing structural damage, reducing the risk of the solid electrolyte interface membrane being repeatedly destroyed and continuously reformed, thereby improving the cycle performance of the battery cell comprising the negative electrode plate.
[0040] In addition, the solid electrolyte interface membrane formed with the participation of chalcogenide materials has good active ion permeability, which can promote the rapid transmission of active ions at the interface and improve the ion transmission rate. After the chalcogenide materials in the functional coating of the negative electrode plate participate in the solid electrolyte interface membrane, the porosity in the functional coating is improved, and the transmission rate of active ions in the negative electrode plate is improved, thereby comprehensively improving the kinetic performance of the battery cell containing the negative electrode plate.
[0041] In a fourth aspect, the present application provides a battery cell, comprising the negative electrode sheet of the first aspect or the second aspect or the negative electrode sheet prepared by the preparation method of the third aspect. The battery cell comprising the negative electrode sheet has at least the advantages of the negative electrode sheet.
[0042] In some optional embodiments, after the battery cell is formed, the functional coating includes 20% to 30% of chalcogen elements based on the total mass of the functional coating, and the chalcogen elements include one or more of sulfur, selenium, and tellurium.
[0043] According to the embodiment of the present application, after the battery cell is formed, the functional coating of the fresh negative electrode sheet contains the above-mentioned content of chalcogen elements, which can exist in the form of particles or porous particles and have a high specific surface area; and the pores formed after the chalcogen material in the fresh negative electrode sheet is decomposed further increase the porosity and specific surface area. Having a high specific surface area can provide more reaction interfaces and active sites, so that the negative electrode sheet has a higher lithium / sodium insertion capacity, and can effectively insert and extract lithium ions or sodium ions, thereby increasing the capacity of the battery cell containing the negative electrode sheet.
[0044] In some optional embodiments, after the battery cell is formed, the porosity of the functional coating is 30% to 60%. According to the embodiment of the present application, due to the increase in the porosity of the functional coating in the negative electrode sheet, the mass energy density and dynamic performance of the battery cell are improved.
[0045] In some optional embodiments, the battery cell includes an electrolyte, and the electrolyte includes a C3-C12 cyclic carbonate.
[0046] According to the embodiment of the present application, the cyclic carbonate of C3-C12 can be one or more of ethylene carbonate (EC), fluoroethylene carbonate, difluoroethylene carbonate, and 2,3-butylene carbonate. The sulfide material of the present application undergoes a reduction reaction during the electrochemical cycle, and can react with the cyclic carbonate compounds of C3-C12 to generate poly(ethylene oxide) (PEO)-type polymers, which participate in the formation of a solid electrolyte interface film on the surface of the negative electrode plate, i.e., the functional coating. The solid electrolyte interface film has excellent elasticity, can effectively accommodate and allow the volume expansion of the negative electrode active material layer and the functional coating at the negative electrode-electrolyte interface, stabilize the interface stability of the negative electrode plate and the electrolyte, and improve the service life of the battery cell.
[0047] In some optional embodiments, the battery cell includes a negative electrode plate and a solid electrolyte interface membrane, the solid electrolyte interface membrane includes 0.01% to 6% of a chalcogenide element based on the total weight of the solid electrolyte interface membrane, wherein the chalcogenide element includes at least one of sulfur, selenium, and tellurium.
[0048] According to the embodiments of the present application, the sulfur elements having the above-mentioned content in the solid electrolyte interface membrane may generate poly(ethylene oxide) (PEO)-type polymers, which help to improve the elasticity of the solid electrolyte interface membrane, and are beneficial for accommodating and allowing a certain amount of volume change of the negative electrode plate during the cycle process.
[0049] In some optional embodiments, the solid electrolyte interface film includes at least one of the compounds represented by formula (1) and formula (2):
[0050]
[0051] Wherein, R represents a chalcogen element, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, and Mo, 0<x'≤2, 0<y'≤1, and n represents a natural number.
[0052] According to the embodiments of the present application, the compound represented by formula (1) has an alkyl group containing 2 carbon atoms, and the carbon atoms thereof are in free rotation, the arrangement of the chain structure and the flexibility of the long-chain alkyl group, so that the solid electrolyte interface membrane containing the compound represented by formula (1) has good elasticity.
[0053] According to the embodiment of the present application, the compound shown in formula (2) itself has an ether bond, and the bond length of the ether bond is relatively large, which allows the compound to undergo a large deformation under the action of an external force, and can return to its original state after the external force is removed. This gives the material a certain elasticity, allowing it to deform without breaking when subjected to force. The ether bond has a low bond energy, which makes the ether bond relatively easy to break, and can rotate freely after breaking, thereby increasing the flexibility of the material. The breaking of the ether bond can cause the material to undergo reversible deformation when subjected to force without causing damage to the material. The oxygen atoms around the ether bond have a high electronegativity and can form intermolecular forces such as hydrogen bonds or van der Waals forces with other molecules or groups. These intermolecular forces can increase the cohesion of the material, making it more ductile, and comprehensively enhance the good elasticity of the solid electrolyte interface film containing the compound shown in formula (2).
[0054] In some optional embodiments, the valence state of the chalcogen element includes at least one of negative one, negative two, positive four, and positive six.
[0055] According to the embodiments of the present application, the sulfide elements exist in the solid electrolyte interface membrane in the above-mentioned valence state, and can form stable chemical bonds in the solid electrolyte interface membrane, enhance the stability of the membrane, and prevent the active ions and electrons in the electrolyte from directly entering the negative electrode active material, thereby reducing the side reactions of the battery. In addition, the presence of the sulfide elements in the above-mentioned valence state in the solid electrolyte interface membrane can exhibit good ionic conductivity, provide a path for the transmission of active ions, and promote the transmission of active ions in the solid electrolyte interface membrane. In addition, the interaction between the sulfide element and other components in the solid electrolyte interface membrane (such as polymers, etc.) can adjust the structure and properties of the solid electrolyte interface membrane and increase the transmission rate of active ions in the solid electrolyte interface membrane.
[0056] In some optional embodiments, after the battery monomer is formed, the ratio of the sum of the molar amounts n1 of tetravalent and hexavalent sulfur elements in the solid electrolyte interface membrane per unit mass to the sum of the molar amounts n0 of sulfur elements in the solid electrolyte interface membrane per unit mass is (0.3-3):1, and can optionally be (0.5-1.5):1.
[0057] According to the embodiments of the present application, the elastic range of the solid electrolyte interface membrane can be quantitatively determined according to the ratio of the sum of the molar amounts of tetravalent and hexavalent sulfur elements in a unit mass of the solid electrolyte interface membrane n1 to the sum of the molar amounts of sulfur elements in a unit mass of the solid electrolyte interface membrane n0, so that a negative electrode active material layer with a suitable volume expansion can be designed according to the elastic solid electrolyte interface membrane, thereby avoiding the expansion of the negative electrode active material layer of the negative electrode plate affecting the electrochemical performance of the battery cell.
[0058] In a fifth aspect, the present application provides an electrical device, including the battery cell of the first aspect or the second aspect. The battery cell or electrical device of the present application includes the negative electrode sheet of the first aspect or the second aspect of the present application, and thus has at least the advantages of using the negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0060] Figure 1 A schematic diagram showing an embodiment of a battery cell of the present application.
[0061] Figure 2 Shows Figure 1 An exploded schematic diagram of a battery cell is shown.
[0062] Figure 3 A schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source is shown.
[0063] In the drawings, the drawings are not necessarily drawn to scale. DETAILED DESCRIPTION
[0064] Below, the negative electrode plate and its preparation method, electrode assembly battery cell, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0065] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, characterized in that a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0066] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0067] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0068] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0069] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0070] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0071] Unless otherwise specified, in this application, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0072] If not specifically stated otherwise, in this application, the term "attach" refers to connection by adhesion, coating or the like.
[0073] If not otherwise specified, in this application, the terms "first", "second", "third", "fourth", etc. are used to distinguish different objects rather than to describe a specific order or a primary and secondary relationship.
[0074] Unless otherwise specified, in this application, the term "active ions" refers to ions that can be inserted and removed back and forth between the positive and negative electrodes of a battery cell, including but not limited to lithium ions, sodium ions, etc.
[0075] The term "several" or "multiple" used in the present application refers to two or more (including two).
[0076] The battery cells mentioned in the embodiments of the present application may be lithium-ion batteries, sodium-ion batteries, lithium metal batteries, sodium metal batteries, etc., but the embodiments of the present application are not limited to this.
[0077] The battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. The electrode sheet will expand in volume during the static and formation process after the electrolyte is injected, which will increase the overall thickness of the battery and affect the battery performance. During the formation process of the battery cell, the electrode sheet expands. The reasons include volume expansion and stress relaxation expansion caused by the combination of active ions with electrode material particles (such as adsorption, embedding or combination). Studies have found that in the subsequent charging process after the battery is formed, the negative electrode sheet will also expand in volume. The main reason is that the active ions migrate from the positive electrode sheet to the negative electrode sheet and combine with the negative electrode active material (such as adsorption, embedding or combination), which increases the volume of the negative electrode active material, thereby causing the volume expansion of the negative electrode sheet.
[0078] When the volume of the negative electrode plate expands, the plate is squeezed and generates a large internal stress. Such internal stress may cause damage to the internal materials of the plate (such as damage to the active material particles), deformation of the battery casing, etc. The repeated volume expansion / contraction of the negative electrode plate during the charge and discharge process may also lead to repeated destruction and generation of the solid electrolyte interface membrane (SEI membrane), which is not conducive to the stability of the solid electrolyte interface membrane and further affects the cycle performance of the battery. In short, the repeated volume expansion / contraction of the electrode plate, especially the negative electrode plate, during the charge and discharge process of the battery has an adverse effect on the cycle performance of the battery, which is a challenge to improving the cycle performance of the battery. For the negative electrode plate containing silicon-based negative electrode materials, the volume expansion effect is more obvious.
[0079] In order to reduce the impact of the volume expansion of the negative electrode sheet on the cycle performance of the battery, the current measures mainly involve improving the structure of the active material itself to reduce its volume expansion and contraction effect during the battery charging and discharging process. However, research has found that the improvement of the structure of the active material itself for this purpose is subject to many restrictions such as the range of active material options and capacity requirements, and cannot solve the problem of volume expansion of the electrode sheet caused by other factors (such as the deposition of active ions outside the active material).
[0080] In view of this, the technical solution of the embodiment of the present application provides a negative electrode plate, which can at least reduce the adverse effects of repeated volume expansion / contraction of the negative electrode plate during the battery charging and discharging process on the cycle performance of the battery, thereby improving the cycle performance of the battery cell containing it.
[0081] Negative electrode
[0082] In a first aspect, an embodiment of the present application provides a negative electrode sheet, comprising:
[0083] Negative electrode current collector,
[0084] a negative electrode active material layer disposed on at least one side of the negative electrode current collector; and
[0085] The functional coating is disposed on the side of the negative electrode active material layer away from the negative electrode current collector, wherein the functional coating comprises a chalcogenide material, and the chalcogenide material comprises elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
[0086] The technical solution of the embodiment of the present application provides a negative electrode sheet, wherein the negative electrode active material layer of the negative electrode sheet is provided with a functional coating on the side away from the negative electrode current collector, and the functional coating comprises a specific chalcogenide material. Unexpectedly, when a battery cell comprising the negative electrode sheet according to the embodiment of the present application is formed, an SEI film having excellent elasticity and stability can be formed on the surface of the negative electrode sheet.
[0087] Without intending to be limited to any theory or explanation, when the above-mentioned battery cell is formed, the functional coating contacts and interacts with the electrolyte (including a cyclic carbonate solvent such as ethylene carbonate), so that the sulfide material participates in the formation of the SEI film. The components of the SEI film formed thereby may include alkyl sulfates and polyoxyalkylene polymers (such as polyethylene oxide (PEO)), etc., so that the SEI film has excellent elasticity and stability. Such an SEI film can accommodate and adapt to the large volume change of the negative electrode sheet containing the negative electrode active material layer, reduce or avoid the negative electrode sheet squeezing the structure containing the SEI film in the battery cell and thus causing structural damage, reduce the risk of the SEI film being repeatedly damaged and continuously re-formed, and thus improve the cycle performance of the battery cell containing the negative electrode sheet.
[0088] In addition, the solid electrolyte interface membrane with excellent elasticity can stabilize the interface stability between the negative electrode plate and the electrolyte, thereby increasing the service life of the battery cell.
[0089] In addition, the solid electrolyte interface membrane formed with the participation of chalcogenide materials has good active ion permeability, which can promote the rapid transmission of active ions at the interface and improve the ion transmission rate. After the chalcogenide materials in the functional coating of the negative electrode plate participate in the solid electrolyte interface membrane, the porosity in the functional coating is improved, and the transmission rate of active ions in the negative electrode plate is improved, thereby comprehensively improving the kinetic performance of the battery cell containing the negative electrode plate.
[0090] According to the embodiment of the present application, x and y in the chalcogenide material can be understood as the molar ratio of element M to chalcogenide elements including sulfur, selenium, and tellurium. In some embodiments, the ratio of x to y can be 1:(0-2). As an example, the chalcogenide material includes molybdenum disulfide.
[0091] Sulfur materials often exist in the form of particles or porous materials and have a high specific surface area. The high surface area can provide more reaction interfaces and active sites, so that the negative electrode plate has a higher lithium / sodium insertion capacity and can effectively insert and deinsert lithium ions or sodium ions, thereby increasing the capacity of the battery cell containing the negative electrode plate.
[0092] M in Chalcogenide Materials x S y 、M x Sey 、M x Te y It has certain electronic conductivity, but its electrical conductivity is low, and it usually has a sub-stoichiometric composition, that is, the ratio of metal and sulfur elements including selenium deviates from the stoichiometric ratio. This sub-stoichiometric ratio can provide more embedding / de-embedding sites, promote faster ion transport and higher electrochemical reaction rates, and improve the electrochemical reaction kinetics of the battery cell to achieve high power output and fast charge and discharge rates.
[0093] Elemental sulfur, elemental selenium, and elemental tellurium in chalcogenide materials are non-metallic elements, which are usually connected in the form of covalent bonds in the crystal structure. The formation of covalent bonds allows sulfur and selenium to form a relatively stable structure in the crystal, but it also restricts the free movement of electrons, and their electronic conductivity is poor. When they exist in the negative electrode plate, it is beneficial to improve the safety performance of the negative electrode plate.
[0094] In some optional embodiments, the functional coating includes 30% to 95% of the chalcogenide material based on the total mass of the functional coating.
[0095] Optionally, the functional coating includes a mass content of 30%, 31%, 32%, 33%, 34%, 35%, 36%,
[0096] 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%,
[0097] 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%,
[0098] 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%,
[0099] 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%,
[0100] A chalcogenide material having any numerical value of 89%, 90%, 91%, 92%, 93%, 94%, or 95%, or a range of a composition thereof.
[0101] According to the embodiments of the present application, the sulfide material containing the above-mentioned mass content can improve the elasticity of the solid electrolyte interface membrane, can accommodate and adapt to large volume changes of the negative electrode pole piece containing the negative electrode active material layer, reduce or avoid the negative electrode pole piece squeezing the structure containing the solid electrolyte interface membrane in the battery cell and thereby causing structural damage, reduce the risk of the solid electrolyte interface membrane being repeatedly destroyed and continuously reformed, thereby improving the cycle performance of the battery cell containing the negative electrode pole piece.
[0102] In some optional embodiments, the ratio of the thickness of the negative electrode active material layer to the thickness of the functional coating layer is 1:
[0103] (0.01~0.2), can be selected as 1:(0.01~0.1).
[0104] According to the embodiment of the present application, the ratio of the thickness of the negative electrode active material layer to the thickness of the functional coating layer is controlled within the above range, so that the functional coating layer can provide a sufficient protective layer to protect the negative electrode active material. The components such as metal selenide, sulfur and selenium can form a protective layer to prevent the negative electrode active material from directly contacting the electrolyte, reduce the side reaction with the electrolyte, and improve the cycle stability of the battery cell containing the negative electrode plate.
[0105] The thickness ratio of the negative electrode active material layer to the functional coating can affect the transmission path and resistance of electrons and ions. Generally speaking, a smaller ratio may help improve ion transport and electron conductivity, thereby improving the discharge performance and charging rate of the battery.
[0106] In some optional embodiments, the thickness of the functional coating is 1-10 um; optionally, 2-5 um. Optionally, the thickness of the functional coating can be any value of 1 um, 2 um, 3 um, 4 um, 5 um, 6 um, 7 um, 8 um, 9 um, 10 um or a range thereof.
[0107] According to the embodiment of the present application, the functional coating has a thickness within the above range, which is beneficial to the embedding and de-embedding of active ions of the negative electrode plate in the battery cell, and is beneficial to the dynamic performance and cycle performance of the battery cell.
[0108] When the thickness of the functional coating is too high, the remaining unreacted non-conductive chalcogenide material will coat the surface of the electrode, increasing the surface impedance, hindering the transmission of active ions, and affecting the capacity of the active material and the cycle stability; when the thickness of the functional coating is too low, the elasticity improvement effect of the solid electrolyte interface film formed by the chalcogenide material is limited, limiting its ability to accommodate the volume expansion of the negative electrode.
[0109] In some optional embodiments, the average particle size D50 of the chalcogenide material is 0.05-25 um; optionally, 0.1-5 um.
[0110] Optionally, the average particle size D50 of the chalcogenide material may be 0.05um, 0.10um, 0.15um, 0.20um,
[0111] 0.25um, 0.30um, 0.35um, 0.40um, 0.45um, 0.50um, 0.55um, 0.65um, 0.70um,
[0112] 0.75um, 0.80um, 0.85um, 0.90um, 0.95um, 1.0um, 1.5um, 2.0um, 2.5um, 3.0um,
[0113] 3.5um, 4.0um, 4.5um, 5.0um, 5.5um, 6.0um, 6.5um, 7.0um, 7.5um, 8.0um, 8.5um, 9.0um, 9.5um, 10.0um, 10.5um, 11.0um, 11.5um, 12.0um, 13.0um, 13.5um,
[0114] 14.0um, 14.5um, 15.0um, 16.0um, 16.5um, 17.0um, 17.5um, 18.0um, 18.5um,
[0115] Any value among 19.0um, 19.5um, 20.0um or a range composed of these values.
[0116] According to the embodiments of the present application, the average particle size Dv50 of the chalcogenide material is within the above range, which is beneficial for the chalcogenide material to participate in the formation of a solid electrolyte interface film during the formation of the battery cell, and to form evenly distributed pores with relatively uniform particle size after decomposition from the negative electrode active material layer, which is beneficial to the structural stability of the functional coating and the dynamic performance and cycle performance of the battery cell.
[0117] Volume average particle size D v 50 is a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured by instruments and methods well-known in the art. For example, it can be conveniently measured by a laser particle size analyzer with reference to the particle size distribution laser diffraction method of GB / T19077-2016, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0118] In some optional embodiments, the porosity of the functional coating is 15% to 40%.
[0119] Optionally, the porosity of the functional coating can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%,
[0120] 35%, 36%, 37%, 38%, 39%, 40% or any range thereof. According to the application embodiment, the functional coating has a porosity within the above range, which is conducive to the electrolyte infiltration of the functional coating during the formation stage, and facilitates the chalcogenide material in the functional coating to participate in the formation of the solid electrolyte interface film, thereby making the solid electrolyte interface film have stronger elasticity.
[0121] In some optional embodiments, the functional coating includes a chalcogenide material, a conductive agent, and a binder.
[0122] According to an embodiment of the present application, when the functional coating comprises a chalcogenide material, a conductive agent and a binder. x S y 、M x Se y 、M x Te y It can be used as negative electrode active material, with high lithium / sodium insertion capacity, and the entire functional coating can be used as another new negative electrode active material layer to improve the cycle performance of the battery cell. Sulfur, selenium and tellurium in chalcogenide materials can also be used as negative electrode active materials.
[0123] In some optional embodiments, the functional coating includes 5% to 10% of the conductive agent based on the total mass of the functional coating.
[0124] Alternatively, the functional coating may include any value of 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% or a combination thereof of the conductive agent.
[0125] According to the embodiments of the present application, when the functional coating contains the conductive agent in the above-mentioned content, the internal resistance of the negative electrode plate can be reduced, and the internal resistance of the entire battery cell can be reduced, which is beneficial to the transmission of electrons and improves the dynamic performance of the battery cell containing the negative electrode plate.
[0126] In some optional embodiments, the functional coating comprises 3% to 5% of a binder based on the total mass of the functional coating. Optionally, the functional coating comprises 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% of a binder.
[0127] According to the embodiment of the present application, when the functional coating has the above-mentioned binder content, the structural stability, electrical conductivity and ion transport performance of the negative electrode plate can be balanced. However, too high or too low a binder content may affect the performance of a battery cell including the negative electrode plate.
[0128] In some optional embodiments, based on the total mass of the functional coating, the functional coating includes 80% to 95% of a simple substance of a chalcogen element and 5% to 20% of a binder, and the chalcogen element includes at least one of sulfur, selenium, and tellurium. Optionally, the functional coating may include 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 80%,
[0129] A conductive agent having any value or a range of its composition among 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 19.5%, and 20%. According to an embodiment of the present application, the functional coating comprises the above-mentioned content of the simple substance of the chalcogen element and the above-mentioned content of the binder. When the negative electrode sheet comprising the above-mentioned functional coating is chemically formed, the functional coating only comprises the simple substance of the chalcogen element and the binder, as well as the gaps left by the consumption of part of the simple substance of the chalcogen element. The coating has an insulating effect and can enhance the safety performance of the battery cell comprising the negative electrode sheet.
[0130] In some optional embodiments, based on the total mass of the functional coating, the functional coating comprises 85% to 92% of a chalcogenide material containing a metal element, 5% to 10% of a conductive agent, and 3% to 5% of a binder, wherein the chalcogenide material containing a metal element comprises M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
[0131] According to an embodiment of the present application, the functional coating comprises the above-mentioned content of a chalcogenide material containing a metal element, the above-mentioned content of a conductive agent and the above-mentioned content of a binder. When the negative electrode plate comprising the above-mentioned functional coating is formed, the functional coating has a larger porosity. The chalcogenide material containing a metal element as a negative electrode active material has good electronic conductivity and can quickly transfer electrons. It usually has a sub-stoichiometric composition, that is, the ratio of metal to chalcogenide elements including selenium deviates from the stoichiometric ratio. This sub-stoichiometric ratio can provide more embedding / de-embedding sites, promote faster ion transport and higher electrochemical reaction rates, and can improve the electrochemical reaction kinetics of the battery cell to achieve high power output and fast charge and discharge rates.
[0132] In some optional embodiments, the negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon, a silicon-carbon composite material, and a silicon-oxygen material.
[0133] According to the embodiment of the present application, the negative electrode active material layer including the above silicon-based material is in the negative electrode plate, which can improve the capacity of the battery cell including the negative electrode plate and realize rapid ion diffusion.
[0134] In some optional embodiments, the negative electrode active material layer includes 1% to 50% silicon based on the total mass of the negative electrode active material layer. Optionally, the negative electrode active material layer includes 1%, 2%, 3%, 4%, 5%, 6%, 7%,
[0135] 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%,
[0136] 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%,
[0137] Silicon element in an amount of any numerical value among 48%, 49%, and 50%, or a range of the composition thereof.
[0138] According to the embodiment of the present application, adding the above-mentioned silicon element can increase the capacity of the negative electrode active material, thereby improving the energy density of the battery. Silicon has a high electrical conductivity, and adding an appropriate amount of silicon element can enhance the electronic conductivity of the negative electrode active material layer; silicon-based materials have a high ion diffusion coefficient, and the introduction of an appropriate amount of silicon element can promote the rapid transmission of active ions in the negative electrode active material, thereby improving the battery's kinetic performance, including the charge and discharge rate.
[0139] The specific composition and structure of the negative electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited to this.
[0140] For example, when the battery cell is a lithium-ion battery cell or a sodium-ion battery cell, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0141] The negative electrode active material is a material that can extract and embed active ions (such as lithium ions, sodium ions, etc.), and the negative electrode active material can adopt materials known in the art. As an example, the negative electrode active material includes but is not limited to one or more of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. Silicon-based materials may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy materials. Tin-based materials may include one or more of elemental tin, tin oxide and tin alloy materials. The present application is not limited to these materials, and other conventionally known materials that can be used as negative electrode active materials may also be used.
[0142] In some embodiments, the negative electrode active material layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0143] In some embodiments, the negative electrode active material layer may further include a negative electrode binder. The present application has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). One or more.
[0144] In some embodiments, the negative electrode active material layer may further include other auxiliary agents. As an example, the other auxiliary agents may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, and the like.
[0145] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0146] The negative electrode active material layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0147] The negative electrode plate does not exclude other additional layers besides the negative electrode active material layer and the functional coating of the present application. For example, in some embodiments, the negative electrode plate of the present application may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate of the present application may also include a protective layer covering the surface of the negative electrode active material layer.
[0148] When the battery cell is a lithium metal battery cell, the negative electrode plate may not include negative electrode active materials capable of extracting and embedding active ions. For example, in some embodiments, the negative electrode plate may include a lithium plate or a lithium alloy plate; in other embodiments, the negative electrode plate includes a mesh or foam three-dimensional skeleton layer, such as foam copper (or copper alloy), foam nickel (or nickel alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, etc.
[0149] When the battery cell is a sodium metal battery cell, the negative electrode plate may not include negative electrode active materials capable of extracting and embedding active ions. For example, in some embodiments, the negative electrode plate may include a sodium plate or a sodium alloy plate; in other embodiments, the negative electrode plate includes a mesh or foam three-dimensional skeleton layer, such as foam copper (or copper alloy), foam nickel (or nickel alloy), foam aluminum (or aluminum alloy), copper (or copper alloy) mesh, nickel (or nickel alloy) mesh, aluminum (or aluminum alloy) mesh, etc.
[0150] Method for preparing negative electrode sheet
[0151] In a third aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising:
[0152] A first slurry containing a chalcogenide material and a second slurry containing a positive electrode active material are provided, wherein the chalcogenide material includes elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2;
[0153] The first slurry and the second slurry are coated on one side of the negative electrode current collector to form a functional coating and a negative electrode active material layer, respectively, to obtain the negative electrode plate of the first aspect or the second method, wherein the negative electrode plate includes a negative electrode active material layer arranged on at least one side of the negative electrode current collector and a functional coating arranged on a side of the negative electrode active material layer away from the current collector.
[0154] According to the embodiments of the present application, by respectively forming a functional coating and a negative electrode active material layer with a composition comprising a chalcogenide material and a positive electrode active material, the chalcogenide material in the negative electrode plate can participate in forming a solid electrolyte interface membrane. The solid electrolyte interface membrane has the participation of chalcogenide elements, which enhances the elasticity of the solid electrolyte interface membrane and can accommodate and adapt to large volume changes of the negative electrode plate comprising the negative electrode active material layer, thereby reducing or avoiding the negative electrode plate squeezing the structure comprising the solid electrolyte interface membrane in the battery cell and thereby causing structural damage, reducing the risk of the solid electrolyte interface membrane being repeatedly destroyed and continuously reformed, thereby improving the cycle performance of the battery cell comprising the negative electrode plate.
[0155] In addition, the solid electrolyte interface membrane formed with the participation of chalcogenide materials has good active ion permeability, which can promote the rapid transmission of active ions at the interface and improve the ion transmission rate. After the chalcogenide materials in the functional coating of the negative electrode plate participate in the solid electrolyte interface membrane, the porosity in the functional coating is improved, and the transmission rate of active ions in the negative electrode plate is improved, thereby comprehensively improving the kinetic performance of the battery cell containing the negative electrode plate.
[0156] Battery Cell
[0157] In a fourth aspect, the present application provides a battery cell, comprising the negative electrode sheet of the first aspect or the second aspect or the negative electrode sheet prepared by the preparation method of the third aspect. The battery cell comprising the negative electrode sheet has at least the advantages of the negative electrode sheet.
[0158] The present application has no particular restrictions on the type of battery cells, for example, the battery cells may be lithium ion batteries, sodium ion batteries, etc. Optionally, sodium ion batteries may be used.
[0159] In some optional embodiments, after the battery cell is formed, the functional coating includes 20% to 30% of chalcogen elements based on the total mass of the functional coating, and the chalcogen elements include one or more of sulfur, selenium, and tellurium.
[0160] Optionally, the functional coating may include 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% of the chalcogen element based on the total mass of the functional coating.
[0161] According to the embodiment of the present application, after the fresh negative electrode plate undergoes chemical formation, the functional coating contains the above-mentioned content of chalcogen elements, which can exist in the form of particles or porous particles and have a high specific surface area; and the pores formed after the chalcogen material in the fresh negative electrode plate is decomposed further increase the porosity and specific surface area. Having a high specific surface area can provide more reaction interfaces and active sites, so that the negative electrode plate has a higher lithium / sodium insertion capacity, and can effectively insert and extract lithium ions or sodium ions, thereby increasing the capacity of the battery cell containing the negative electrode plate.
[0162] The chalcogenide elements in the embodiments of the present application can be in the form of single substance or in the form of M x S y 、M x Se y 、M x Te y Sulfur materials usually have a relatively stable crystal structure, which can maintain the integrity and stability of the structure during battery cycles, thereby improving the cycle stability of battery cells containing the sulfur materials and maintaining a high capacity retention rate and energy efficiency during multiple charge and discharge cycles.
[0163] M x S y 、M x Se y 、M x Te y The chalcogenides in the form have certain electronic conductivity properties, and they usually have a sub-stoichiometric composition, that is, the ratio of metals and chalcogenides including selenium deviates from the stoichiometric ratio. This sub-stoichiometric ratio can provide more embedding / de-embedding sites, promote faster ion transport and higher electrochemical reaction rates, and improve the electrochemical reaction kinetics of the battery cell to achieve high power output and fast charge and discharge rates.
[0164] Sulfur, selenium, and tellurium are non-metallic elements that are usually connected in the form of covalent bonds in the crystal structure. The formation of covalent bonds allows sulfur and selenium to form a relatively stable structure in the crystal, but it also restricts the free movement of electrons, and their electronic conductivity is poor. When they exist in the negative electrode plate, they are beneficial to improving the safety performance of the negative electrode plate.
[0165] In some optional embodiments, after the battery cell is formed, the porosity of the functional coating is 30% to 60%. According to the embodiment of the present application, due to the increase in the porosity of the functional coating in the negative electrode sheet, the mass energy density and dynamic performance of the battery cell are improved.
[0166] In some optional embodiments, the battery cell includes an electrolyte, and the electrolyte includes a C3-C12 cyclic carbonate.
[0167] According to the embodiment of the present application, the cyclic carbonate of C3-C12 can be one or more of ethylene carbonate (EC), fluoroethylene carbonate, difluoroethylene carbonate, and 2,3-butylene carbonate. The sulfide material of the present application undergoes a reduction reaction during the electrochemical cycle, and can react with the cyclic carbonate compounds of C3-C12 to generate poly(ethylene oxide) (PEO)-type polymers, which participate in the formation of a solid electrolyte interface film on the surface of the negative electrode plate, i.e., the functional coating. The solid electrolyte interface film has excellent elasticity, can effectively accommodate and allow the volume expansion of the negative electrode active material layer and the functional coating at the negative electrode-electrolyte interface, stabilize the interface stability of the negative electrode plate and the electrolyte, and improve the service life of the battery cell.
[0168] In some optional embodiments, the battery cell includes a negative electrode plate and a solid electrolyte interface membrane, the solid electrolyte interface membrane includes 0.01% to 6% of a chalcogenide element based on the total weight of the solid electrolyte interface membrane, wherein the chalcogenide element includes at least one of sulfur, selenium, and tellurium.
[0169] Optionally, the solid electrolyte interface film includes 0.01%, 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.5%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, based on the total weight of the solid electrolyte interface film. 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0% of any value or composition range of the chalcogenide element.
[0170] According to the embodiments of the present application, the sulfur elements having the above-mentioned content in the solid electrolyte interface membrane may generate poly(ethylene oxide) (PEO)-type polymers, which help to improve the elasticity of the solid electrolyte interface membrane, and are beneficial for accommodating and allowing a certain amount of volume change of the negative electrode plate during the cycle process.
[0171] In some optional embodiments, the solid electrolyte interface film includes at least one of the compounds represented by formula (1) and formula (2):
[0172]
[0173] Wherein, R represents a chalcogen element, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, and Mo, 0<x'≤2, 0<y'≤2, and n represents a natural number.
[0174] According to the embodiments of the present application, the compound represented by formula (1) has an alkyl group containing 2 carbon atoms, and the carbon atoms thereof are in free rotation, the arrangement of the chain structure and the flexibility of the long-chain alkyl group, so that the solid electrolyte interface membrane containing the compound represented by formula (1) has good elasticity.
[0175] According to the embodiment of the present application, the compound shown in formula (2) itself has an ether bond, and the bond length of the ether bond is relatively large, which allows the compound to undergo a large deformation under the action of an external force, and can return to its original state after the external force is removed. This gives the material a certain elasticity, allowing it to deform without breaking when subjected to force. The ether bond has a low bond energy, which makes the ether bond relatively easy to break, and can rotate freely after breaking, thereby increasing the flexibility of the material. The breaking of the ether bond can cause the material to undergo reversible deformation when subjected to force without causing damage to the material. The oxygen atoms around the ether bond have a high electronegativity and can form intermolecular forces such as hydrogen bonds or van der Waals forces with other molecules or groups. These intermolecular forces can increase the cohesion of the material, making it more ductile, and comprehensively enhance the good elasticity of the solid electrolyte interface film containing the compound shown in formula (2).
[0176] As an example, reactants generated by the reaction of the chalcogenide material are shown in reaction formulas 1 to 3.
[0177]
[0178] Among them, 0<x≤2.
[0179] According to the embodiments of the present application, under the action of the sulfide material of the present application, on the basis of reaction formula 1, reactions of reaction formula 2 and reaction formula 3 continue to occur, so that the solid electrolyte interface membrane includes more compounds shown in formula (1) and also has compounds shown in formula (2) that can effectively improve the elasticity of the solid electrolyte interface membrane, so the sulfide material significantly improves the elasticity of the solid electrolyte interface membrane.
[0180] According to the embodiments of the present application, sulfides can exhibit good ionic conductivity under certain conditions. In the solid electrolyte interface membrane, sulfides can serve as a channel or bridge for ion transmission, provide a path for active ion transmission, and promote the transmission of active ions in the solid electrolyte interface membrane. In addition, the interaction between sulfides and other components in the solid electrolyte interface membrane (such as polymers, etc.) can regulate the structure and properties of the solid electrolyte interface membrane and increase the transmission rate of active ions in the solid electrolyte interface membrane.
[0181] In addition, sulfides can form stable chemical bonds in the solid electrolyte interface film, enhance the stability of the film, and prevent active ions and electrons in the electrolyte from directly entering the negative electrode active material, thereby reducing the side reactions of the battery.
[0182] In some optional embodiments, the valence state of the chalcogen element includes at least one of negative one, negative two, positive four, and positive six.
[0183] According to the embodiment of the present application, the valence state of the chalcogenide elements includes +4 and / or +6, and the S2p spectrum peak is 168-172eV; the valence state of the chalcogenide elements includes -2 to -1 / 4, and the S2p spectrum peak is 160-166eV. The above spectrum peaks are obtained by disassembling the battery cell after formation and taking the anode electrode for XPS testing.
[0184] According to the embodiments of the present application, the sulfide elements exist in the solid electrolyte interface membrane in the above-mentioned valence state, and can form stable chemical bonds in the solid electrolyte interface membrane, enhance the stability of the membrane, and prevent the active ions and electrons in the electrolyte from directly entering the negative electrode active material, thereby reducing the side reactions of the battery. In addition, the presence of the sulfide elements in the above-mentioned valence state in the solid electrolyte interface membrane can exhibit good ionic conductivity, provide a path for the transmission of active ions, and promote the transmission of active ions in the solid electrolyte interface membrane. In addition, the interaction between the sulfide element and other components in the solid electrolyte interface membrane (such as polymers, etc.) can adjust the structure and properties of the solid electrolyte interface membrane and increase the transmission rate of active ions in the solid electrolyte interface membrane.
[0185] In some optional embodiments, after the battery monomer is formed, the ratio of the sum of the molar amounts n1 of tetravalent and hexavalent sulfur elements in the solid electrolyte interface membrane per unit mass to the sum of the molar amounts n0 of sulfur elements in the solid electrolyte interface membrane per unit mass is (0.3-3):1, and can optionally be (0.5-1.5):1.
[0186] Optionally, the ratio of n1 to n0 can be any value or a range of its composition among 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1.
[0187] According to the embodiments of the present application, the elastic range of the solid electrolyte interface membrane can be quantitatively determined according to the ratio of the sum of the molar amounts of tetravalent and hexavalent sulfur elements in a unit mass of the solid electrolyte interface membrane n1 to the sum of the molar amounts of sulfur elements in a unit mass of the solid electrolyte interface membrane n0, so that a negative electrode active material layer with a suitable volume expansion can be designed according to the elastic solid electrolyte interface membrane, thereby avoiding the expansion of the negative electrode active material layer of the negative electrode plate affecting the electrochemical performance of the battery cell.
[0188] [Positive electrode]
[0189] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector and including a positive active material. For example, the positive current collector has two surfaces opposite to each other in its thickness direction, and the positive active material layer is disposed on any one or both of the two opposite surfaces of the positive current collector.
[0190] The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material may be a positive electrode active material for a battery cell known in the art.
[0191] For example, when the battery cell is a lithium-ion battery cell or a lithium metal battery cell, the positive electrode active material may include one or more of a lithium transition metal oxide, a lithium-containing phosphate with an olivine structure, and their respective modified compounds. Examples of lithium transition metal oxides may include one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates with an olivine structure may include one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds. The present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials may also be used.
[0192] In some embodiments, in order to further improve the energy density of the battery cell, the positive electrode active material may include a general formula of Li a Ni b Co c M d O e A f One or more of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes one or more selected from Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes one or more selected from N, F, S and Cl.
[0193] As an example, the positive electrode active material may include LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811), LiNi0.85 Co 0.15 Al 0.05 O 2 、LiFePO 4 and LiMnPO 4 One or more of .
[0194] When the battery cell is a sodium ion battery cell or a sodium metal battery cell, the positive electrode active material may include but is not limited to one or more of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0195] As an example, the positive electrode active material may include NaFeO 2 、NaCoO 2 、NaCrO 2 、NaMnO 2 、NaNiO 2 、NaNi 1 / 2 Ti 1 / 2 O 2 、NaNi 1 / 2 Mn 1 / 2 O 2 、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O 2 、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、NaFePO 4 、NaMnPO 4 、NaCoPO 4 , Prussian blue materials and general formula X p M' q (PO 4 ) r O x Y 3-x In the general formula X p M' q (PO 4 ) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes a selection from H + , Li + 、Na + , K + and NH 4 +One or more of, M' is a transition metal cation, which may be selected from one or more of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, which may be selected from one or more of F, Cl and Br.
[0196] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.
[0197] In some embodiments, the positive electrode active material layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0198] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0199] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0200] The positive electrode active material layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0201] [Electrolytes]
[0202] In some embodiments, the battery cell includes an electrolyte. The electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).
[0203] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0204] The type of electrolyte salt is not specifically limited and can be selected according to actual needs. For example, the electrolyte salt includes one or more selected from lithium salts for lithium ion batteries and sodium salts for sodium ion batteries. As an example, the lithium salt includes one or more selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorobis(oxalate phosphate) (LiDFOP), lithium tetrafluorooxalate phosphate (LiTFOP). As an example, the sodium salt includes one or more selected from NaPF 6 、NaClO 4 、NaBCl 4 、NaSO 3 CF 3 、Na(CH 3 )C 6 H 4 SO 3 One or more of the .
[0205] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include one or more selected from ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0206] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0207] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0208] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0209] The present application has no particular restrictions on the shape of the battery cell, which can be a flat body, a rectangular parallelepiped or other shapes. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.
[0210] In some embodiments, Figure 2 As shown, the outer packaging may include a shell 51 and a cover plate 53. It is characterized in that the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate together form a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 of the first aspect of the embodiment of the present application or the electrode assembly 52 prepared by the method according to the second aspect of the embodiment of the present application is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0211] The method for preparing the battery cell of the present application is well known, and the method at least includes the step of preparing the electrode assembly of the second aspect of the embodiment of the present application. In some embodiments, the electrode assembly can be placed in an outer package, injected with electrolyte after drying, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a battery cell.
[0212] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.
[0213] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of battery cells are accommodated in the accommodation space.
[0214] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0215] [Preparation method]
[0216] The preparation method of the battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying. After packaging, standing, forming, shaping and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.
[0217] Electrical devices
[0218] In a fifth aspect, the present application provides an electrical device, including the battery cell of the first aspect or the second aspect. The battery cell or electrical device of the present application includes the negative electrode sheet of the first aspect or the second aspect of the present application, and thus has at least the advantages of using the negative electrode sheet.
[0219] The battery cell can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0220] Figure 3 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.
[0221] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0222] Example
[0223] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0224] Example 1
[0225] Preparation of positive electrode
[0226] Will Li[Ni 0.9 Co 0.05 Mn 0.05 ]O 2 The abbreviation (NCM90 ternary material), conductive agent carbon black, binder polyvinylidene fluoride (PVDF), and carbon nanotubes (CNT) are dry-mixed and stirred at a weight ratio of 77.3:10:8.7:2.7:1.3, stirred and mixed at a speed of 400-1000 r / s, and then wetted, kneaded and dispersed to obtain positive electrode slurry. The obtained slurry is then coated on aluminum foil, dried, cold pressed, and cut to obtain the positive electrode sheet of Example 1.
[0227] Preparation of negative electrode
[0228] Preparation of active material layer coating slurry: Active material artificial graphite, silicon oxide, conductive agent carbon black, binder styrene butadiene rubber (SBR), thickener sodium hydroxymethyl cellulose (CMC-Na) in a weight ratio of 72.2:25:0.8:0.8:1.2 are dry-mixed evenly, and then deionized water is added to mix evenly to prepare an active layer slurry.
[0229] Preparation of functional coating slurry: dry-mix elemental sulfur powder, carbon nanotubes, and binder styrene-butadiene rubber (SBR) in a weight ratio of 90:7:3, and then add deionized water to mix evenly to prepare a functional coating slurry.
[0230] Preparation of composite negative electrode sheets: The precursor of the active material layer is evenly coated on the current collector, and the active material layer is obtained by drying at a temperature of 90°C for 15 minutes; the precursor of the functional coating is evenly printed on the active material layer with a gravure roller, and the functional coating is obtained by drying at a temperature of 60°C for 35 minutes. The thickness of the functional coating is 3um, and the composite negative electrode sheet is obtained after cold pressing and slitting.
[0231] Preparation of isolation membrane
[0232] A polyethylene film is used as the isolation film.
[0233] Preparation of electrolyte
[0234] In an argon atmosphere glove box (H 2 O<0.01ppm, O 2 <0.01ppm), organic solvents ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 4 / 6, and 12.5% LiPF 6 The lithium salt is dissolved in the organic solvent and stirred evenly to obtain the electrolyte of Example 1.
[0235] Preparation of lithium-ion battery cells
[0236] The prepared positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, with the isolation film placed between the positive and negative electrode sheets, and then wound to obtain a bare battery cell; the bare battery cell is placed in a battery outer package, and then injected with electrolyte, packaged, allowed to stand, formed, shaped, and capacity tested to complete the preparation of the lithium-ion battery, wherein the lithium-ion battery has a thickness of 14.2 mm, a width of 32 mm, and a length of 82 mm.
[0237] Examples 2-1 to 2-14: The preparation method is similar to that of Example 1, except that the types of chalcogenide materials are different, see Table 1 for details.
[0238] Examples 3-1 to 3-8: The preparation method is similar to that of Example 1, except that the content of the chalcogenide material in the functional coating in the preparation steps is different, see Table 1 for details.
[0239] Examples 4-1 to 4-4
[0240] The preparation method is similar to that of Example 1, except that the particle size of the chalcogenide material in the functional coating is different, as shown in Table 1.
[0241] Examples 5-1 to 5-6
[0242] The preparation method is similar to that of Example 1, except that the thickness ratio of the functional coating layer to the negative electrode active material layer is different, as shown in Table 1 for details.
[0243] Comparative Example 1
[0244] The difference between this comparative example and Example 1 is: Preparation of the negative electrode sheet: dry-mix the active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC-Na) in a weight ratio of 97.2:0.8:0.8:1.2, and then add deionized water to mix evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0245] Test Section
[0246] 1) Detection method of the content of chalcogenide materials in the functional coating: First, the positive electrode is digested with a digestion reagent: concentrated nitric acid (HNO 3 ) and concentrated hydrochloric acid (HCl) in a volume ratio of 1:1 to digest with aqua regia. The digestion method can be: plate / acid digestion / microwave digestion (high temperature and high pressure is about 200°C). Then collect the digested solution and put it into the inductively coupled plasma spectrometer for testing, and the chalcogen content can be quantitatively measured.
[0247] 2) DC internal resistance test method: At 25°C, charge the shipped lithium-ion battery and the lithium-ion battery that has been cycled 100 times at 45°C to 4.25V at a constant current of 0.33C, then charge at a constant voltage of 4.25V until the current is less than 0.05C, and then discharge at 0.33C for 30 minutes, that is, adjust the battery cell's power to 50% SOC. Then touch the positive and negative probes of the TH2523A AC internal resistance tester to the positive and negative electrodes of the battery respectively, and read the internal resistance of the battery through the internal resistance tester, which are recorded as the initial battery cell internal resistance and the battery cell internal resistance after 100 cycles.
[0248] 3) The test method for 0.33C capacity retention rate is: at 25°C, charge the lithium-ion battery at 0.33C constant current to 4.25V, then charge at 4.25V constant voltage to a current less than 0.05C, and then discharge the lithium-ion battery at 0.33C constant current to 3.0V. This is a charge and discharge process. Repeat the charging and discharging process in this way, and calculate the capacity retention rate of the lithium-ion battery after 100 cycles.
[0249] Capacity retention rate (%) of lithium ion battery after 100 cycles at 25° C. = (discharge capacity at 100th cycle / discharge capacity at first cycle)×100%.
[0250] 4) Test method for 60℃ storage capacity retention rate:
[0251] The battery capacity recovery rate test process is as follows: before storage, at 25°C, the battery corresponding to implementation 1 is charged to 4.25V at a constant current of 1 / 3C, then charged to 0.05C at a constant voltage of 4.25V, left for 30 minutes, and then discharged to 2.8V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. After storage at 60°C for 100 days, the battery temperature is cooled to room temperature, and the above steps are repeated. The measured capacity is recorded as Cr, and the battery capacity recovery rate after storage for 50 days is H=Cr / C0*100%.
[0252] 5) 0.33C overcharge failure boundary test method:
[0253] First, the battery cell is installed on the fixture, then fully charged at 0.33C to 100% SOC, the sample appearance is checked and photographed, and the battery cell OCV, IMP, and mass are recorded; then, the battery cell is charged at 0.33C at room temperature until the cell fails, the battery cell SOC status at this time is recorded, and the battery voltage change is monitored simultaneously.
[0254] 6) Fully charged shallow puncture safety boundary test method:
[0255] First, the battery cell is installed on the fixture, and then fully charged to 100% SOC at 0.33C. The appearance of the sample is checked and photographed, and the OCV, IMP, and mass of the battery cell are recorded. This is carried out at room temperature. The nail has a diameter of 1mm and a speed of 0.1mm / s. It is inserted at a uniform speed perpendicular to the direction of the battery plate. The insertion position is close to the geometric center of the punctured surface. The battery cell is punctured until it fails, and the penetration depth at this time is recorded.
[0256] 7) Fast charging performance (10%-80% SOC fast charging time)
[0257] The test process of 10%-80% SOC charging time is as follows: at 25°C, the batteries in the embodiment and comparative example are charged from 10% SOC to 80% SOC at 1.0C / 0.8C / 0.5C / 0.33C step by step. The charging time when no lithium deposition occurs at the negative electrode is the fast charging time of the battery at this time. The shorter the fast charging time, the better the fast charging performance of the battery.
[0258] Test Results
[0259] Based on the test results of Examples 1 to 8, it can be seen that the functional coating of the negative electrode plate contains a chalcogenide material, which improves the cycle performance of the battery cell containing the negative electrode plate, the high temperature storage performance and the safety of the battery cell.
[0260] The reason may be that when the battery cell is formed, the functional coating contacts and interacts with the electrolyte (containing a cyclic carbonate solvent such as ethylene carbonate), so that the sulfide material participates in the formation of the SEI film. The components of the SEI film formed may include alkyl sulfates and polyoxyalkylene polymers (such as polyethylene oxide (PEO)), etc., so that the SEI film has excellent elasticity and stability. Such an SEI film can accommodate and adapt to the large volume changes of the negative electrode sheet containing the negative electrode active material layer, reduce or avoid the negative electrode sheet squeezing the structure containing the SEI film in the battery cell and causing structural damage, reduce the risk of the SEI film being repeatedly destroyed and continuously re-formed, thereby improving the cycle performance of the battery cell containing the negative electrode sheet. The solid electrolyte interface film with excellent elasticity can stabilize the interface stability between the negative electrode sheet and the electrolyte, and improve the service life of the battery cell. Sulfur materials often exist in the form of particles or porous materials and have a high specific surface area. The high surface area can provide more reaction interfaces and active sites, so that the negative electrode plate has a higher lithium / sodium insertion capacity and can effectively insert and deinsert lithium ions or sodium ions, thereby increasing the capacity of the battery cell containing the negative electrode plate.
[0261] M in Chalcogenide Materials x S y 、M x Se y 、M x Te y It has certain electronic conductivity, but its electrical conductivity is low. The elemental sulfur, elemental selenium, and elemental tellurium in the chalcogenide materials are non-metallic elements, which are usually connected in the form of covalent bonds in the crystal structure. The formation of covalent bonds allows sulfur and selenium to form a relatively stable structure in the crystal, but it also limits the free movement of electrons, and its electronic conductivity is poor. When it exists in the negative electrode plate, it is beneficial to improve the safety performance of the negative electrode plate. According to Table 1, compared with Comparative Example 1, the functional coating of the negative electrode set in the embodiment includes a chalcogenide material, which improves the cycle performance of the battery cell containing the negative electrode plate, the service life and safety of the battery cell.
[0262] Compared with Example 1, Examples 2-1 to 2-14 have different types of chalcogenide materials and thus have differentiated cycle performance, high-temperature storage performance, and safety performance.
[0263] According to Table 1, compared with Example 1, the chalcogenide material content in Examples 3-1 to 3-8 is reduced, which leads to a decrease in their high temperature storage performance and 0.33C overcharge failure boundary performance.
[0264] According to Table 1, compared with Examples 4-1 to 4-4, the smaller the average particle size DV50 of the chalcogenide material in the functional coating in Example 4, the better the capacity retention rate after 100cls of cycling and the capacity retention rate after 50days of storage, indicating that the smaller the average particle size DV50, the better the cycle performance and high temperature storage performance of the battery cell.
[0265] According to Table 1, compared with Examples 5-1 to 5-6, the ratio of the thickness of the functional coating layer to the thickness of the negative electrode active material layer in Example 1 is different, which affects the cycle performance of the battery cell containing the negative electrode plate, the high temperature storage performance and safety of the battery cell to a certain extent. The smaller the ratio of the thickness of the functional coating layer to the thickness of the negative electrode active material layer, the safety performance is improved as the relative thickness of the functional coating layer in Examples 5-4 and 5-6 increases. Compared with Comparative Example 1, it was tested that the charging time of the examples in Example 1, Example 5-1 and Example 5-3 was faster than that in Comparative Example 1, and the fast charging performance in the example group increased with the increase of the thickness of the negative electrode active material layer, and the charging time was shorter.
[0266] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
[0267]
[0268]
[0269]
Claims
1. A negative electrode plate, characterized in that: include: Negative electrode current collector, A negative electrode active material layer, disposed on at least one side of the negative electrode current collector; and The functional coating is disposed on the side of the negative electrode active material layer away from the negative electrode current collector, wherein the functional coating comprises a chalcogenide material, and the chalcogenide material comprises elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
2. The negative electrode sheet according to claim 1, characterized in that: The functional coating includes 30% to 95% of the chalcogenide material based on the total mass of the functional coating.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The ratio of the thickness of the negative electrode active material layer to the thickness of the functional coating layer is 1:(0.01-0.2), optionally, 1:(0.01-0.1).
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The thickness of the functional coating is 1 to 10 um; optionally, 2 to 5 um.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The average particle size D50 of the chalcogenide material is 50 to 500 nm; optionally, 100 to 300 nm.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The porosity of the functional coating is 15% to 40%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The functional coating comprises a chalcogenide material, a conductive agent and a binder.
8. The negative electrode sheet according to claim 7, characterized in that: Based on the total mass of the functional coating, the functional coating comprises 5% to 10% of a conductive agent; and / or, The functional coating includes 3% to 5% of a binder based on the total mass of the functional coating.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: Based on the total mass of the functional coating, the functional coating comprises 85% to 92% of a chalcogenide material containing a metal element, 5% to 10% of a conductive agent, and 3% to 5% of a binder, wherein the chalcogenide material containing a metal element comprises M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2.
10. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: The negative electrode active material layer includes a silicon-based material, and the silicon-based material includes one or more of silicon single substance, silicon-carbon composite material, and silicon-oxygen material; Optionally, based on the total mass of the negative electrode active material layer, the negative electrode active material layer includes 1% to 50% of silicon.
11. A method for preparing a negative electrode sheet, characterized in that: include: A first slurry containing a chalcogenide material and a second slurry containing a positive electrode active material are provided, wherein the chalcogenide material includes elemental sulfur, elemental selenium, elemental tellurium, M x S y 、M x Se y 、M x Te y One or more of, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, Mo, 0<x≤2, 0<y≤2; The first slurry and the second slurry are coated on one side of the negative electrode current collector to form a functional coating and a negative electrode active material layer, respectively, to obtain the negative electrode plate according to any one of claims 1 to 10, wherein the negative electrode plate comprises the negative electrode active material layer arranged on at least one side of the negative electrode current collector and the functional coating arranged on the side of the negative electrode active material layer away from the current collector.
12. A battery cell, characterized in that: It comprises the negative electrode sheet according to any one of claims 1 to 10 or the negative electrode sheet prepared by the preparation method according to claim 11.
13. The battery cell according to claim 12, characterized in that: After the battery monomer is formed, the functional coating comprises 20% to 30% of the chalcogen element based on the total mass of the functional coating; and / or, After the battery monomer is formed, the porosity of the functional coating is 30% to 60%.
14. The battery cell according to claim 12 or 13, characterized in that: The battery cell includes an electrolyte, and the electrolyte includes a C3-C12 cyclic carbonate.
15. The battery cell according to any one of claims 12 to 14, characterized in that: It comprises a negative electrode plate and a solid electrolyte interface film, wherein the solid electrolyte interface film comprises 0.01% to 6% of chalcogen elements by mass, wherein the chalcogen elements comprise at least one of sulfur, selenium and tellurium.
16. The battery cell according to claim 15, characterized in that: The solid electrolyte interface film comprises at least one of the compounds represented by formula (1) and formula (2): Wherein, R represents the chalcogen element, M includes one or more of Li, Na, Mg, Fe, Co, Ni, Cu, Ti, and Mo, 0<x'≤2, 0<y'≤2, and n represents a natural number.
17. The battery cell according to claim 15 or 16, characterized in that: The valence state of the chalcogen element includes at least one of negative monovalent, negative divalent, positive tetravalent and positive hexavalent.
18. The battery cell according to claim 17, characterized in that: After the battery cell is formed, the ratio of the sum of the molar amounts n1 of the tetravalent and hexavalent sulfide elements in the solid electrolyte interface membrane per unit mass to the sum of the molar amounts n0 of the sulfide elements in the solid electrolyte interface membrane per unit mass is (0.3-3):1, and can be optionally (0.5-1.5):
1.
19. An electrical device, characterized in that: A battery cell comprising the battery cell according to any one of claims 12 to 18.
Citation Information
Patent Citations
Lithium secondary battery and cathode plate thereof
CN102593416A
Lithium ion battery and negative electrode piece thereof
CN109560247A
Ternary lithium ion battery capable of discharging to 0 V and preparation method thereof
CN112652761A
Negative electrode active material, process for preparing the same, and battery, battery module, battery pack and apparatus related to the same
US20220123314A1
